1999
DOI: 10.1093/ajcp/112.2.179
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Needle Aspiration Biopsy of Soft Tissue Sarcomas: A Cytomorphologic Analysis With Emphasis on Histologic Subtyping, Grading, and Therapeutic Significance

Abstract: A b s t r a c tAlthough fine-needle aspiration biopsy (FNAB) of soft tissue sarcomas has been used effectively for preoperative evaluation and documentation of local recurrences and metastases, its role in the initial diagnosis of primary soft tissue sarcomas is still not accepted widely. 12 In experienced hands, sensitivity and specificity rates exceed 90% for the determination of malignancy and approach the rates obtained with frozen section interpretation.3 -4 Nevertheless, the accuracy and therapeutic sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0
4

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 7 publications
3
70
0
4
Order By: Relevance
“…Most important, a needle biopsy should be used to establish the presence of malignancy and to determine whether a lesion is mesenchymal. From our data and that published within the literature, [3][4][5][6][7][8][9][10][11][12] FNA appears to perform many of the same functions as core needle biopsy.…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…Most important, a needle biopsy should be used to establish the presence of malignancy and to determine whether a lesion is mesenchymal. From our data and that published within the literature, [3][4][5][6][7][8][9][10][11][12] FNA appears to perform many of the same functions as core needle biopsy.…”
Section: Resultssupporting
confidence: 54%
“…[3][4][5][6][7][8][9][10][11] Some of these studies have addressed the accuracy of FNA in histologic subtyping of mesenchymal tumors. [3][4][5][6][7][8][9][10][11] The success of subtyping tumors of the musculoskeletal system has varied among studies but generally has been between 50% and 70% accurate. 6 -10, 12 Some authors have demonstrated greater accuracy of subclassification for bone neoplasms, 12 whereas others have shown significantly less success with subclassification of soft tissue neoplasms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4). Die Anwendung der Zusatzuntersuchungen bei den überwiegend aus runden Zellen bestehenden Weichteitumoren führt im höchsten Prozentsatz (bis zu 83%) der Fälle im Vergleich mit anderen Grundmustern zu definitiver Subtypisierung [17].…”
Section: Runde Zellenunclassified
“…offene Biopsien beurteilt. Bis auf einige technische Einzelheiten stehen ihm grundsätzlich die gleichen Zusatzuntersuchungen zur Verfü-gung [10,11,15,17]. Insbesondere der Einsatz der Zellblocktechnik lässt den scheinbaren Widerspruch zwischen einer FNP und einer Stanzbiopsie in vielen Fällen schwinden -die Bearbeitung, die diagnostischen Kriterien und die zur Verfügung stehenden Methoden sind identisch [30,32].…”
Section: Bedeutung Von Zusatzuntersuchungenunclassified